Pemanfaatan Media Canva dalam Pembelajaran Biologi untuk Meningkatkan Hasil Belajar Siswa SMA - Regina Futri; Agista Rahmadani; Rezki Septiya Ningsih Rahiki; Selviana Selviana; Adis Adelia Saputri; A. S. Alonemarera (Educatoria : Jurnal Ilmiah Ilmu Pendidikan, 2026)
Canva was used to enhance high school biology learning in this study. Biology is abstract, making it difficult for students to understand, especially when taught with a boring approach. Therefore, interactive and innovative learning media are needed. Google Scholar was used to obtain and analyze scientific articles for this Systematic Literature Review (SLR). The search yielded 10 scientific articles on Canva-based learning media with empirical evidence. The results of this study indicate that the use of Canva-based learning media in high school biology learning consistently has a high level of validity and practicality, and is effective in improving student learning outcomes. Based on a synthesis of various studies, Canva has been shown to have a significant impact on improving cognitive learning outcomes (indicated by high N-gain values ​​and good learning outcomes), as well as strengthening affective aspects such as student motivation, creativity, and enthusiasm. The use of visual and audiovisual elements in Canva helps facilitate the understanding of abstract biological concepts, thus supporting more active, interactive, and student-centered learning. Therefore, the use of Canva as a high school biology learning medium can improve student learning outcomes.